2001
DOI: 10.21236/ada444161
|View full text |Cite
|
Sign up to set email alerts
|

Detonation Initiation Studies and Performance Results for Pulsed Detonation Engine Applications

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Dayton, OH 45440Abstract An in-house computational and experimental program to investigate and develop an air breathing pulse detonation engine (PDE) that uses a practical fuel (kerosene based, fleet-wide use, "JP" type) is curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 2 publications
2
69
0
Order By: Relevance
“…The rise time of the pressure is within the order of 10 À5 s. The pressure spikes of transducer 11 are much smaller than transducer 10's. This indicates that PDE operated in a partially-filled mode [21][22][23]. There was no gasoline/air mixture near the location of transducer 11 when the detonation wave arrived here.…”
Section: Pde Results Without Ejectormentioning
confidence: 89%
“…The rise time of the pressure is within the order of 10 À5 s. The pressure spikes of transducer 11 are much smaller than transducer 10's. This indicates that PDE operated in a partially-filled mode [21][22][23]. There was no gasoline/air mixture near the location of transducer 11 when the detonation wave arrived here.…”
Section: Pde Results Without Ejectormentioning
confidence: 89%
“…Eqs. (5) and (6) are suitable for the range of β cr ≤β≤1. In other words, detonable mixture section length must be longer than that of deflagration to detonation transition, otherwise detonation cannot be achieved.…”
Section: Engineering Thermophysicsmentioning
confidence: 99%
“…While the PDE presents a mechanically simple device, its unsteady thermo-fluid dynamics are quite complex. As may be expected with such a relatively new technology, the study on the approaches for achieving optimum design and performance is only at the initial stage and needs further exploration.In the past few years, numerous studies on the effects of partial mixture filling on PDE performance have been reported analytically, numerically and experimentally [5][6][7][8][9][10][11][12] . Zitoun et al [5] measured the single-cycle impulse of ethylene-oxygen mixtures under standard conditions in a detonation tube and an extension with the same cylindrical cross section.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus combustible mixtures formation and deflagration or detonation initiation in poly-dispersed fuel-air mixtures are the key aspects providing different limitations for operation of those engines. Onset of detonation being very dangerous for conventional engines could, however, serve the basis for creating new generation of engines-pulse detonating engines (PDE) [1][2][3]. Dispersed mixtures having been formed by different pulverizers could not be spatially uniform.…”
Section: Introductionmentioning
confidence: 99%